Ameliorating effect of Ghrelin on nicotine induced oxidative stress in liver tissue morphology in BALB/c mice. - Pervez Kiyani, Hira; Ahsin, Sadia; Imran, Madiha; Ayaz, Hira (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nicotine, a naturally occurring alkaloid is the predominant chemical among the constituents in cigarette smoke. Consumption forms include smoke (cigarettes, pipes and cigars) and smokeless tobacco (chewable tobacco). Aim: To determine the effect of ghrelin in nicotine induced liver toxicity in BALB/c mice. Study Design: Randomized Control Trial. Methodology: Present study enrolled 90 male BALB/c mice Group I (control group) was given standardized laboratory diet and intraperitoneal injection (i.p) of normal saline. Group II was given standardized laboratory diet and nicotine at a dose of 2.5mg/ kg body weight (i.p), while Group III was given standardized laboratory diet plus nicotine a dose of 2.5mg/ kg body weight (i.p) along with ghrelin at a dose of 10µg/kg on alternate days for 4 weeks. On 30th day sampling was done for hepatic tissue oxidative stress enzymes (superoxide dismutase, glutathione reductase and catalase levels), and histology of liver tissue for assessment of hepatic tissue damage and recovery. Results: Nicotine group showed evident hepatic damage with significant increase in liver oxidative stress markers. On histological examination, liver showed mild to moderate grade necro-inflammation. Administration of ghrelin partially restored the oxidative stress markers and inflammatory histological changes due to nicotine induced toxicity. Conclusion: We concluded that Ghrelin appears to be hepatoprotective due to its antioxidant and anti-inflammatory properties.